Software-defined wireless sensor networks: A survey. (1st October 2018) - Mostafaei, Habib; Menth, Michael
Abstract: Software-defined networking (SDN) decouples data and control plane, i.e., forwarding elements are remotely configured by centralized controllers instead through distributed control protocols. Wireless sensor networks (WSNs) have mostly been controlled in a distributed way, but its configuration challenges are complex and can be theoretically better solved with network-wide knowledge – the solution just needs to be configured on the distributed sensor nodes. This calls for SDN in WSNs and so that software-defined WSNs (SD-WSNs) have been proposed. In this survey, we explain basics of WSN and SDN, describe fundamentals of SD-WSNs and how SDN can improve the operation of WSN. Furthermore, we outline the open challenges that need to be investigated in more detail and discuss lessons learned during the preparation this survey.